2002
DOI: 10.1046/j.1475-1313.2002.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐related optical aspects of the onset of presbyopia

Abstract: Evidence is presented which substantiates the frequent clinical impression that female optometric patients require their first reading prescription at a slightly earlier age than males. Furthermore newly presbyopic females require an initial add of slightly greater magnitude than age-matched males. A high (>+1.50 D) first add requirement is revealed as a predominantly male characteristic, an outcome attributable essentially to their often relatively later age of presentation for an initial presbyopic refractiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…He found the average adult refraction to be +1.25 D. Several authors, however, believe the normal refractive limit of the eye to be 0.50 D. Nathan (1957) stated that small errors are usually taken as being any ametropia not exceeding 0.50 D in either principal meridian, and both Tassman (1932), and Jackson (1932) defined emmetropia as being 0.50 D or less. This view is in agreement with Gullstrand, who in Helmholtz's Treatise on Physiological Optics (1924) stated that the limit of normal astigmatism in the eye was 0.50 DC, and Pointer (2002) who believed that a reading addition of less than +0.50 D would be of ‘doubtful clinical necessity’. Cholerton (1955) found it more difficult to define emmetropia: he reminds us that the spherical aberration of the eye may be greater than 0.50 D, and that chromatic aberration alone amounts to 0.85 D. This fact may explain why Adamson and Fincham (1939) found that there is a physiological tolerance to ametropia of between 0.25 and 0.50 D without any compensatory change in accommodation: they reported that perceptual tolerance (the amount by which the accommodation varies for a given object distance without blur) can be as high as 1.25 D in some subjects.…”
Section: Introductionsupporting
confidence: 85%
“…He found the average adult refraction to be +1.25 D. Several authors, however, believe the normal refractive limit of the eye to be 0.50 D. Nathan (1957) stated that small errors are usually taken as being any ametropia not exceeding 0.50 D in either principal meridian, and both Tassman (1932), and Jackson (1932) defined emmetropia as being 0.50 D or less. This view is in agreement with Gullstrand, who in Helmholtz's Treatise on Physiological Optics (1924) stated that the limit of normal astigmatism in the eye was 0.50 DC, and Pointer (2002) who believed that a reading addition of less than +0.50 D would be of ‘doubtful clinical necessity’. Cholerton (1955) found it more difficult to define emmetropia: he reminds us that the spherical aberration of the eye may be greater than 0.50 D, and that chromatic aberration alone amounts to 0.85 D. This fact may explain why Adamson and Fincham (1939) found that there is a physiological tolerance to ametropia of between 0.25 and 0.50 D without any compensatory change in accommodation: they reported that perceptual tolerance (the amount by which the accommodation varies for a given object distance without blur) can be as high as 1.25 D in some subjects.…”
Section: Introductionsupporting
confidence: 85%
“…12 There is evidence that age-related changes in certain ocular parameters, including corneal curvature, endothelial changes, and the onset of presbyopia, can be different between men and women. 7,13,14 In a recent study, we observed a trend toward a decrease in the central and peripheral IOP measured with rebound tonometry, 15 although sex did not seem to have a significant effect. 16 Intraocular lens design, laser excimer algorithm computation, and IOP-correcting factors after corneal refractive surgery require knowledge of several ocular parameters at different ages.…”
mentioning
confidence: 65%
“…7 The average 60-year-old European adult has minimal accommodation and relies on depth of focus or artificial assistance such as spectacles to enable clear and comfortable near vision. 5,7 The exact age that near vision spectacles are required depends on a range of factors such as individual variation in accommodative ability, 8 distance refraction, 9,10 climate, [11][12][13][14][15] geographic location, 12,16,17 demands and expectations, 18 sex, [17][18][19][20][21] and ethnicity. [22][23][24][25][26][27] It has been argued that studies of factors affecting presbyopia are prone to the effects of confounding variables, 16,28 but there does seem to be general acceptance of earlier onset in people with higher melanin levels in equatorial regions.…”
Section: Methodsmentioning
confidence: 99%